The Exploitation of Yugoslav Industry by the Third Reich during World War II - Živković, Nikola (Studia Historiae Oeconomicae, 1979)
This study explores the systematic exploitation of Yugoslav industry by Nazi Germany during World War II. Prior to the war, Yugoslavia possessed an underdeveloped but strategically significant industrial sector, largely controlled by foreign capital. With the German occupation beginning in April 1941, this industrial base was rapidly repurposed to serve the needs of the Third Reich’s war economy. The aim of the research is to analyze how German occupation forces dismantled, relocated, and redirected Yugoslav industrial production, and to assess the broader consequences for the country’s economic and social structure. The study draws on wartime German and Yugoslav documents, postwar reparations commission reports, economic records, and contemporary scholarly sources. A detailed, sector-by-sector account is provided, covering mining, metallurgy, textiles, chemicals, construction materials, and more. Findings show that German authorities not only transported massive quantities of machinery, raw materials, and finished goods to Germany but also enforced the reactivation of many plants under German control. Occupying forces installed their own managers (often Volksdeutsche or Germans) and designated Yugoslav factories as vital to the German war effort. The article also documents the scale of plunder — including thousands of freight cars of equipment and materials — and the severe disruption of local industrial development. Furthermore, the exploitation was often brutal and economically one-sided, with little to no compensation, use of forced or underpaid labor, and near-total disregard for the long-term viability of Yugoslav industry. The legacy of this exploitation left deep scars on the postwar economic landscape of the region. This case study contributes to a broader understanding of wartime economic imperialism, revealing the extent to which Nazi Germany relied on occupied territories not only for strategic resources but for full-scale industrial capacity.